ANALISIS EVALUASI LULUSAN DAN PERSEPSI LINGKUNGAN TERHADAP MINAT MAHASISWA DENGAN PERSEPSI PRIBADI SEBAGAI VARIABEL MODERATING PADA PENDIDIKAN PROFESI AKUNTANSI - Khuzaini Khuzaini (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2010)
Accounting Education Profession is a new program that offered by STIESIA as profession education, therefore, there is a need to find out whether Personal Perception is a moderating variable or not in the relation between Environment Perception and Graduate Evaluation to Student Interest. Data is collected from 110 samples and they are collected with random sampling method, the total of population is 150 persons, total of sample with level = 5% is 105 (Sugiyono, 2006), therefore the number of sample is enough. Questionnaire consists of 4 variables that is Personal Perception with 3 indicators, those are curriculum, teacher and supporting facilities, then Graduate Evaluation with 3 indicators, those are Working Field, Income and Career, and then Environment Perception with 3 indicators, those are parents reference, close friend reference and university teacher reference, with final variable is university student interest with 2 indicators, those are commitment and financing. In this research, its residual parameter is negative, but its influence is not significant, therefore, it can be concluded that personal perception is not a moderating variable, because it is only fulfilling 1 criteria that is parameter with negative sign, but it does not fulfill other criteria that is having significant influence.